2020
DOI: 10.1007/s00198-020-05739-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and complications, readmissions, and mortality after hip fracture

Abstract: Low vitamin D in patients with hip fracture is common. In the present study 407 of 872 (47%) patients had serum calcidiol less than 50 nmol/L. Patients with low vitamin D had more delirium, more new hip fractures and more medical readmissions, but not more orthopaedic complications after 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…[21] Therefore, the delirium in vitamin D deficient patients may be due to increased in- flammation in brain. [19] We also found that preoperative vitamin D deficient group had a higher risk of pneumonia than preoperative vitamin D sufficient group in hip fracture patients. There have been no studies associating preoperative vitamin D deficiency and pneumonia after hip fracture surgery.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…[21] Therefore, the delirium in vitamin D deficient patients may be due to increased in- flammation in brain. [19] We also found that preoperative vitamin D deficient group had a higher risk of pneumonia than preoperative vitamin D sufficient group in hip fracture patients. There have been no studies associating preoperative vitamin D deficiency and pneumonia after hip fracture surgery.…”
Section: Discussionmentioning
confidence: 51%
“…reported that 51% of hip fracture patients had delirium and the concentration of vitamin D (25[OH]D) was lower than controls in their case-control study. Ingstad et al [ 19 ] reported that 21% of the preoperative vitamin D deficient group and 15% of preoperative vitamin D sufficient group were diagnosed with delirium. The risk of delirium was significantly high in vitamin D deficient group (OR, 1.48; 95 CI, 1.04–2.12; P =0.03).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low vitamin D (< 50 nmol/L) at admission for hip fracture increased the risk of delirium, new hip fracture, and medical readmission, but not surgical complications in 1122 patients at Oslo University Hospital, Norway [ 17 ]. On the other hand, persons with higher levels (≥ 75 nmol/L) who had prior falls had no benefit in lower extremity function and were associated with an increased risk of falls [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the conducted studies do not consider these types of fracture separately [ 65 ]. Apart from death, they may lead to a significant deterioration of the physical condition and loss of independence [ 66 ]. Postmenopausal women are the most significant group in HF incidents.…”
Section: Hip Fracturesmentioning
confidence: 99%